Isolation and selection of endophytic spore-forming bacteria with plant growth promoting properties isolated from Ilex paraguariensis St. Hil. (yerba mate) - Liaczeski, Margarita Ester (2020)
Fil: Laczeski, Margarita Ester. Universidad Nacional de Misiones. Facultad de Ciencias Exactas, Químicas y Naturales. Instituto de Biotecnología Misiones “Dra. María Ebe Reca”. Laboratorio de Biotecnología Molecular; Argentina.